INVESTIGATION OF POLY(LACTIC ACID) (PLA)/TITANIUM CARBIDE (TiC) NANOCOMPOSITE FILMS GAMMA RAY SHIELDING PROPERTIES - Yılmaz, Mücahıt (My University, 2022)
In this study, gamma rays absorption properties of Polylactic Acid (PLA)/Titanium Carbide (TiC) nanocomposite films produced by containing 5% TiC were investigated. In applications where radioactive sources such as industry and medical are used, protection from the harmful effects of radiation is very important. Researches on materials to be used in shielding as an alternative to lead are becoming widespread. Comfortable, easily shaped, thin, durable, non-toxic to the environment and the user are the features sought in an ideal shield materials. For this purpose, the gamma ray absorption properties of the PLA/TiC nanocomposite material and its effect on radiation shielding were investigated. The linear attenuation coefficient value of the sample with different thicknesses was obtained with the NaI(TI) scintillation detector. A monochromatic gamma source, Cs-137 gamma radioisotope with 661.62 keV energy was used as the gamma radiation source. To determine the gamma ray shielding ability of materials Half value layer (HVL), tenth value layer (TVL) and radiation shielding efficiency (RPE) parameters of the material were calculated.
Keywords: Gamma irradiation; linear attenuation coeffients; NaI(Tl); nanocomposite film